Occupational Health and Safety Hazards in Masonry Work in Sharjah City - Mohammad Khadem; Sujan Piya; Mohammad Shamsuzzaman (Journal of Engineering, Project, and Production Management)
As the third largest emirate in the UAE, Sharjah is a fast-urbanizing region that has grown into a principal cultural, commercial, and educational center of the country. Among the major economic activities in Sharjah, masonry work provides the necessary economic lifeline for the Emirate. Nonetheless, some workers are often unaware of the detrimental effects of their manual work activities on their health. Accordingly, this research seeks to explore the existence and extent of occupational health hazards among workers in the masonry industry in Sharjah. A cross-sectional research design has been carried out to gather relevant data from occupational safety and health (OSH) experts, contractors, and consultants, using semi-structured interviews and surveys. The result shows that masonry workers in Sharjah face physical and chemical hazards, which are caused by high temperatures, dust, vibrations, repetitive weight lifting, as well as the loading and unloading of materials. The findings from the physical hazard show that low lights and high sounds are the highest in terms of frequency, whereas falls from heights are the highest in terms of severity. Further, the findings show that dust is the major chemical hazard faced by the masonry workers in terms of frequency, whereas asphyxiation is the highest in terms of severity. The survey that was conducted verifies the analytic hierarchy process results. For instance, asphyxiation is the most severe factor, accounting for 69% average weight, while dust account for 6% average weight which makes it the least severe chemical hazard, despite being the most common chemical factor in masonry work across Sharjah. The high rates of chemical and physical hazard exposures demonstrate that the current OSH regulations in Sharjah are insufficient in addressing the most prior masonry works hazards.